Study on the Influence of Sempervivum tectorum and Melatonin on Glutathion Protective Effects in Rats Blood Exposed to Aluminum Sulphate - Corina Gravila; Florin Muselin; Camelia Tulcan; Mirela Ahmadi – Khoie; Ariana- Bianca Velciov; Georgeta- Sofia Pintilie (Scientific Papers Animal Science and Biotechnologies, 2023)
The present study was carried out to investigate the influence of Sempervivum tectorum aqueous extract and melatonin on reduced glutathione (GSH) protective effect in Wistar albino rat blood exposed to aluminium sulphate- Al2(SO4)3. The rats were divided in one control group (C) and 7 experimental groups (E). The control group received tap water. The experimental rats were feed the following way: E1 group – aluminum sulphate, daily, for 3 months; : E2 group – Sempervivum tectorum, daily, for 3 months; : E3 group – melatonin, daily, for 3 months; : E4 group – aluminum sulphate with Sempervivum tectorum, daily, for 3 months; : E5 group – aluminum sulphate with melatonin, daily, for 3 months; E6 group – aluminum sulphate, daily, for 3 months, and thereafter with Sempervivum tectorum for 1 month; E7 group – aluminum sulphate, daily, for 3 month, and thereafter with melatonin for 1 month. This study showed that Aluminum toxicity induced lower GSH. The oxidative stress caused by aluminum, given individual, is more pronounced than in the case in which aluminum is administered simultaneously with Sempervivum tectorum or melatonin. Decreasing GSH value is very small if Sempervivum tectorum or melatonin is given for one month, three months after the administration of aluminum. Effect induced by melatonin is more favorable than that of Sempervivum tectorum.